2000
DOI: 10.1136/gut.47.5.667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a serotonin 5-HT4 receptor antagonist SB-207266 on gastrointestinal motor and sensory function in humans

Abstract: (Gut 2000;47:667-674)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 34 publications
2
65
0
1
Order By: Relevance
“…The time dependence is identical with that found in rats and humans after treatment with two chemically distinct 5-HT 4 receptor antagonists (4,12,34,35). Additionally, chronic Lys nutritional deficiency increased stress-induced defecation during the second, but neither the first nor the third hour of wrap-restraint stress (24).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The time dependence is identical with that found in rats and humans after treatment with two chemically distinct 5-HT 4 receptor antagonists (4,12,34,35). Additionally, chronic Lys nutritional deficiency increased stress-induced defecation during the second, but neither the first nor the third hour of wrap-restraint stress (24).…”
Section: Discussionsupporting
confidence: 65%
“…Agonists on the 5-HT 4 receptor increase cholinergic transmission (9) and thus contract the smooth muscle in the rat and guinea pig ileum † and the human colon (11). Antagonists on the 5-HT 4 receptor do not affect normal, healthy gut function (12) but prevent the disturbances caused by stress (4) or high 5-HT activity (13). Thus, 5-HT 4 receptor antagonists are promising targets for the treatment of diarrhea-predominant irritable bowel syndrome (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recently introduced 5-HT 4 receptor agonist tegaserod accelerates colonic transit but does not consistently affect sensory function in humans (Coffin et al, 2003;Lacy and Yu, 2002). Although a peripherally acting 5-HT 4 receptor antagonist has been reported to blunt somatic and visceral pain in mice, sensory thresholds to colorectal distension were not affected by inhibition of the 5-HT 4 receptor in humans (Espejo and Gil, 1998;Bharucha et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Selective antagonism at this receptor has been postulated to provide symptomatic relief in patients suffering from IBS-D. In a study of 52 healthy subjects, Piboserod (SB207266), a selective 5-HT4 antagonist, was shown to block the effects of cisapride (5-HT4 agonist) and it tended to delay colonic transit times (P = 0.06) [56] . In a placebo-controlled study of 15 patients with IBS-D, Houghton and colleagues reported that 20 mg of SB207266 significantly improved orocecal transit times and demonstrated a non-statistical trend toward improved rectal sensitivity [57] .…”
Section: -Ht4 Antagonistsmentioning
confidence: 99%